Lessons Learnt From Linking Global Recommendations With Localized Marine Restoration Schemes and Policy Options by Using Mixed Methods - Krause, Gesche; Wolf, Christine; Happe, Anne-Kathrin; Hauck, Jennifer; Buttigieg, Pier Luigi; Fuchs, Nike; Scheve, Jan; König, Claudia; Wittmer, Heidi; Raab, Kristina (Frontiers in Marine Science, 2020)
In order to advance ongoing efforts in the (still emerging) field of marine restoration, different forms of knowledge must be combined: not only the biological and technical aspects of marine restoration, but also the social and cultural dimensions of marine restoration efforts. This calls for a newly combined array of methods that allows for a bridging of these different knowledge dimensions. Drawing on our experiences from the ongoing knowledge transfer processes of the INTERNAS project (Scientific Transfer of the results of INTERNational Assessments in the field of Earth and Environmental Research into the German policy context), we provide an overview of methods that were used to link global recommendations with localized marine restoration schemes and policy options. Using a mixed methods approach, we were able to capture and understand the pathways of knowledge transfer from globally synthesized scientific knowledge to local realities related to protecting and enhancing marine biodiversity in Germany. With this structured knowledge transfer approach, actionable solutions for marine conservation and restoration activities could be tailored to the specific national and regional circumstances. Using participatory methods, framework conditions like ecological, social, legal and sectoral value judgment dimensions can be identified. This allows for the development of concerted solutions and creates a common ground for good governance for marine restoration. When scientists engage not only as experts but also as reflexive facilitators in such participatory processes, it is ensured that more inclusive forms of knowledge are fostered that are necessary to better anticipate the potentials and likely pitfalls that marine restoration efforts may encounter. We conclude that existing knowledge on ecosystems, their goods and services as well as societal expectations need to be understood from the start in any kind of marine restoration effort.